Strategi Pemasaran Usaha Ternak Ayam D2 Parbaungan Kabupaten Serdang Bedagai Melalui Digital Marketing Di Kecamatan - Della Puspita; Widya Cecilia; Yus Afrilia; Miftahuddin Miftahuddin; Kiagus Muhammad Zain Basriwijiya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
In this era of globalization, the native chicken business in Indonesia has such high potential that it is very suitable for business actors and chicken farmers in Indonesia. Designing strategies and ways of marketing processed chicken products is very important in increasing product sales. To meet the public demand for native chicken meat, marketing activities are needed that can distribute the meat from producers to consumers. Where marketing is essentially the flow of goods from producers to consumers. Marketing activities are an important factor that will determine the success of an entrepreneur. This research aims to develop and implement an effective digital marketing strategy for chicken farmers in Parbaungan District, Serdang Bedagai Regency, in order to increase sales and product competitiveness through the use of digital technology. In this study, the method used by the author is a qualitative research method by conducting a case study of the object under study. According to Sugiyono (2019: 16) qualitative research methods are as research methods based on natural philosophy (experiments) where researchers are instruments, data collection techniques and data analysis are inductive / qualitative and emphasize meaning. Word of mouth marketing is a promotional method that comes from consumers, by consumers, and for consumers. Satisfied customers will not only repurchase but they are also a walking, talking billboard for the business.